Design and Analysis of Impedance Pumps Utilizing Electromagnetic Actuation - Yu-Hisang Wang; Yao-Wen Tsai; Chien-Hsiung Tsai; Chia-Yen Lee; Lung-Ming Fu (Sensors, 2010)
This study designs and analyzes an impedance pump utilizing an electromagnetic actuator. The pump is designed to have three major components, namely a lower glass substrate patterned with a copper micro-coil, a microchannel, and an upper glass cover plate attached a magnetic PDMS diaphragm. When a current is passed through the micro-coil, an electromagnetic force is established between the coil and the magnetic diaphragm. The resulting deflection of the PDMS diaphragm creates an acoustic impedance mismatch within the microchannel, which results in a net flow. In performing the analysis, simulated models of the magnetic field, the diaphragm displacement and the flow rate are developed using Ansoft/Maxwell3D, ANSYS FEA and FLUENT 6.3 CFD software, respectively. Overall, the simulated results reveal that a net flow rate of 52.8 μL/min can be obtained using a diaphragm displacement of 31.5 μm induced by a micro-coil input current of 0.5 A. The impedance pump proposed in this study provides a valuable contribution to the ongoing development of Lab-on-Chips (LoCs) systems.